The State and Labor in Modern Japan - Garon, Sheldon M. (Book collections on Project MUSE., 1987)
In this meticulously researched study, Sheldon Garon examines the evolution of Japan's governmental policies toward labor from the late nineteenth century to the present day, and he substantially revises prevailing views which depict relations between the.